2012
DOI: 10.5194/cp-8-1621-2012
|View full text |Cite
|
Sign up to set email alerts
|

A 250 ka oxygen isotope record from diatoms at Lake El'gygytgyn, far east Russian Arctic

Abstract: Abstract. In 2003 sediment core Lz1024 was drilled at Lake El'gygytgyn, far east Russian Arctic, in an area of the Northern Hemisphere which has not been glaciated for the last 3.6 Ma. Biogenic silica was used for analysing the oxygen isotope composition (δ 18 O diatom ) in the upper 13 m long section dating back about 250 ka with samples dominated by one taxa in the < 10 µm fraction (Cyclotella ocellata). Downcore variations in δ 18 O values show that glacial-interglacial cycles are present throughout the cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 87 publications
(114 reference statements)
3
33
0
Order By: Relevance
“…87‰ Douthitt, 1982;De La Rocha, 2003;Wille et al, 2010;. As a result, purity is routinely demonstrated visually (via scanning electron microscopy) and via quantitative assessments of sample geochemistry (e.g., Al 2 O 3 ) (Brewer et al, 2008;Chapligin et al, 2012). These serve, in the first instance, to demonstrate the efficiency of cleaning (SiO 2 :Al 2 O 3 >1) and robustness of reconstructions.…”
Section: Challenges For Palaeo-record Interpretationmentioning
confidence: 99%
“…87‰ Douthitt, 1982;De La Rocha, 2003;Wille et al, 2010;. As a result, purity is routinely demonstrated visually (via scanning electron microscopy) and via quantitative assessments of sample geochemistry (e.g., Al 2 O 3 ) (Brewer et al, 2008;Chapligin et al, 2012). These serve, in the first instance, to demonstrate the efficiency of cleaning (SiO 2 :Al 2 O 3 >1) and robustness of reconstructions.…”
Section: Challenges For Palaeo-record Interpretationmentioning
confidence: 99%
“…Although Swann et al (2007Swann et al ( , 2008 found a small vital effect (isotopic-species effect) in diatom oxygen isotopic composition, studies on both marine (Shemesh et al, 1995) and freshwater diatoms (Shemesh and Peteet, 1998;Rosqvist et al, 1999;Shemesh et al, 2001;Chapligin et al, 2012b), established that vital effects do not influence the isotopic composition of diatoms. As the Two-Yurts Lake contains predominantly two main diatom species (A. subarctica and S. minutulus) in the N10 μm fraction, which are consistently present throughout the core, we assume that δ…”
Section: Vital Effectsmentioning
confidence: 99%
“…Deciphering the climate change as recorded in the lake sediment record is the main goal of various accompanying papers (e.g. Chapligin et al, 2012;Melles et al, 2012). Notwithstanding, understanding the forcing of the Quaternary climate cycles on the EAFD formation might be improved in the future when an age model for core 5011-3 becomes available.…”
Section: Eafd Formation and Regional Tectonicsmentioning
confidence: 99%